KONTRIBUSI PENDAPATAN ISTRI TERHADAP KEBUTUHAN KELUARGA DI KECAMATAN POLOKARTO - Endang Sri Sudalmi & Dewi Ratna Nurhayati (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2008)
ABSTRACT The main issue of the research is that there is a fact about women having a double role in life which are as a housewife and an extra breadwinner. The aim of the research is to find out how far the role and the contribution of pedestrian women in fullfilling the family needs. The method of the research is using description analysis. Respondents are taken district of Polokarto of Mranggen village and Polokarto village. The used analysis method is tabulation analysis. The results gained from the research are: The women contribution income toward the family expenses in Mranggen village is 48,61 percent, while in Polokarto Village is 48,49 percent. These things show us that mother's contribution in improving family's life is important and big.The general main reason of working mother is to support family life.The response of father and children toward working mom is largely positive. Key words : Wife, work and income